2020
DOI: 10.1002/jper.19-0656
|View full text |Cite
|
Sign up to set email alerts
|

The vertical course of bone regeneration in maxillary sinus floor augmentations: A histomorphometric analysis of human biopsies

Abstract: Background: Maxillary sinus floor augmentation (MSFA) is a well-established and predictable augmentation method in severely resorbed maxillae. However, data on the vertical course of bone graft consolidation within the maxillary sinus are rare. The aim of the present study was to quantify the vertical distribution of new bone formation (nBF) in MSFA and to characterize the vertical gradient of bone graft consolidation. Methods: Eighty-five human sinus biopsies were harvested 6 ± 1 months after MSFA. Histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…Our findings indirectly confirmed a very recent investigation evaluating the vertical gradient of bone graft consolidation in biopsies harvested 6 months after lateral sinus augmentation (Beck et al, 2021 ). This latter study showed that %NFMT gradually decreases from sinus floor towards the apical part of the augmentation area: this negative gradient was moderate in the premolar area and steeper in the molar area.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings indirectly confirmed a very recent investigation evaluating the vertical gradient of bone graft consolidation in biopsies harvested 6 months after lateral sinus augmentation (Beck et al, 2021 ). This latter study showed that %NFMT gradually decreases from sinus floor towards the apical part of the augmentation area: this negative gradient was moderate in the premolar area and steeper in the molar area.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Corbella et al hypothesized that if the sinus floor had only a thin layer of cortical bone, a lower percentage of NBF was to be expected, as compared to less atrophic cases in which the additional presence of cancellous bone could guarantee better regeneration potential [ 34 ]. Since the regenerative potential starts from the residual bone, NBF may also be affected by the harvesting technique and by the vertical gradient of graft consolidation in the collected specimens [ 71 ]. Beck et al, analysing histological thin-ground sections, demonstrated that NBF decreased with increasing distance from the residual sinus floor since the residual graft encapsulated by fibrous tissue had remained in the apical part of the augmented area [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the regenerative potential starts from the residual bone, NBF may also be affected by the harvesting technique and by the vertical gradient of graft consolidation in the collected specimens [ 71 ]. Beck et al, analysing histological thin-ground sections, demonstrated that NBF decreased with increasing distance from the residual sinus floor since the residual graft encapsulated by fibrous tissue had remained in the apical part of the augmented area [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healing after periapical lesions is of utmost importance, especially when considering the subsequent treatment plan that can involve implant placement or sinus lifting. The extent of the periapical lesion dictates the size of the osseous defect that results after dental extraction [ 45 ]. As such, the inflammatory infiltrate can play a major role in healing after dental extraction or apical resection [ 11 , 46 ].…”
Section: Discussionmentioning
confidence: 99%